Wieloaspektowa integracja metod rachunkowości zarządczej w nurcie performance management - Nita, Bartłomiej (Multi-Aspectual Integration of Managerial Accounting Methods under Corporate Performance Management, 2009)
The paper deals with the problem of integration of various methods of management accounting under the framework of corporate performance management. In the first part of the article the rationales for the integration are explained and the role played by the managerial accounting methods in performance management is depicted. As a result of those considerations three major aspect of integration are identified. The second part of the paper discusses these aspects, namely: integration oriented toward planning and budgeting, integration enabling performance measurement and reporting and finally integration for the purposes of activity-based management. It is argued that such an integrated approach to design of managerial accounting methods is very useful from the point of view of performance management. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu, 2009, nr 53, s. 82-93